Improvement of Knowledge and Innovation in the Limau Manis Sejahtera Oyster Mushroom Cultivation Group through a Benchmarking in Sungai Sarik, Padang Pariaman: Improvement Of Knowledge And Innovation In The Limau Manis Sejahtera Oyster Mushroom Cultivation Group Through A Benchmarking In Sungai Sarik, Padang Pariaman - Wellyalina, Wellyalina; Meutia Fiana, Risa; Dewi Hayati, PK; Febjislami, Shalati; Pramana Putra, Dian (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2023)
The Limau Manis Farmers Group is a farmer group located in Limau Manis Village, Pauh Subdistrict, Padang City. This farmer group has been engaged in the cultivation of white oyster mushrooms, and its development has been quite successful. Productive economic development can create a sustainable economy and provide a business opportunity that is ready to compete, thus becoming a source of income for farmers. Especially during the COVID-19 pandemic, when many people lost their jobs, making economic needs even more challenging. The oyster mushroom production efforts of this farmer group are capable of producing a considerable amount of oyster mushrooms. However, there are some obstacles and challenges to producing even more oyster mushrooms. This is due to several factors such as (1) the short shelf life of fresh oyster mushrooms; (2) limited knowledge in processing oyster mushroom harvests; (3) funding issues to support oyster mushroom processing activities; (4) the group's limited knowledge of labeling and packaging; and (5) the group's limitations in managing digital marketing. The most common challenge faced is the frequent delay in spawn availability. Furthermore, the high cost of spawn can also reduce the income of the LMS group. Through benchmarking or visits to advanced oyster mushroom cultivation groups such as the De Jamur group in Sungai Sarik, Padang Pariaman, new knowledge can be acquired, and innovations can be found for the LMS group, resulting in improved mushroom productivity in that group compared to before.